Assessment of four commercial disinfectants on Listeria monocytogenes biofilm - Fouladynezhad, Nina (2014)
Listeria monocytogenes is a Gram-positive and rod-shaped foodborne pathogen. Listeriosis which is caused by L. monocytogenes is a life-threatening disease in immunocompromised individuals, pregnant women, fetuses, newborns, and the elderly. The aim of this study was to investigate biofilm forming ability of L. monocytogenes isolates. Microtitre assay was used to measure the amount of biofilm production by ten L. monocytogenes isolates from minced chicken / beef, beef sausages and chicken burgers patties. In this study the efficiency of four selected commercial disinfectants (D1, D2, D3 and D4) on the inhibiting of L. monocytogenes biofilm was assessed by determining the sessile minimum inhibitory concentration (SMIC). The removing curve efficiency of each disinfectant at five different concentration levels (100, 50, 25, 12.5, and 6.25%) was also defined. Results showed that all ten L. monocytogenes isolates were able to form biofilm over 24 h at 20˚C on polystyrene surface (the common surface in food industries) in vitro. Some strains are better biofilm formers compared to others. All strains showed a slight growth in the quantities of attached cells over 48 and 72 h. No reduction was observed in the amount of biofilm after 72 h. All disinfectants (D1, D2, D3, and D4) in five tested concentrations (100, 50, 25, 12.5, and 6.25%) were able to inhibit the L. monocytogenes biofilm. The efficiency of disinfectants in term of inhibiting biofilm formation from the higher to lower was D1, D2, D4, and D3, respectively. Disinfectant (D4) at low concentrations (25, 12.5, and 6.25%) was more effective in inhibiting L. monocytogenes biofilm compared to concentration (50%). It might be as a result of enhancing the penetrating ability of disinfectant into bacterial cell wall at low concentration levels. Results showed that all four commercial disinfectants were able to effectively inhibit formation of L. monocytogenes biofilm. However, they are not effective in removing biofilm from the surface especially in low concentration levels. Disinfectant D1 showed the highest efficiency on inhibiting L. monocytogenes biofilm formation (up to 95%) at all concentration levels (100, 50, 25, 12.5, and 6.25%). Sessile minimum inhibitory concentration (SMIC) for D1 was found to 6.25%. Sodium dodecylbenzenesulfonate, and trichlorocyanuric acid were effective compounds of D1. The efficiency of D1 declined after the formation of biofilm to considerable level. Implementation of disinfectants at poultry and meat processing factories can reduce the risk of L. monocytogenes biofilm formation and subsequently decrease human health hazards. To sum up, L. monocytogenes have ability to form biofilm in 24 h and the formation of biofilm raising the resistant of L. monocytogenes hence reduce the efficiency of disinfectants in to considerable level in cleaning procedure.